Drought risks for the soybean crop in Rio Grande do Sul state, Brazil - da Mota, Fernando Silveira (Pesquisa Agropecuaria Brasileira, 1992)
Utilizing methods already developed - daily soil moisture balance and derived drought index for soybeans (Glycine max. Merril) - a weather-yield-technology model, with R2 = 0,94, was stablished to evaluate the risks of drought for the soybean yields in Rio Grande do Sul State. A drought index of 40 determines important decreases in yield, and has a probability to occur 1 to 95 times every 100 years, according to the region. A drought index of 68 or more causes crop failure, occurring 95 times every 100 to 1 time every 1000 years according to the region. In the drier climate of the southern region of the state in soils with 200 mm or more of available water capacity the most severe droughts occur 1 time every 100 years and in soils with lower available water capacity such droughts may occur until 95 times each 100 years. In the north region of the state, with more summer rainfall, the probability of drought varies from 5 times every 100 (Missões region) to 1 time every 1000 years (Planalto and Serra do Nordeste regions) for most soil types.